Impact of Germination period on Bioactive compounds and Vitamin contents in Quinoa, Amaranth and Brown Rice - Nam, Jung-Hwan; Park, Soojin (International Journal of Engineering and Technology, 2019)
The present study aimed to determine changes in the activities of digestive enzymes and contents of bioactive substances and antioxidant activities in quinoa, amaranth, and brown rice according to the germination period. Grains were germinated in water for 6 h followed by sprouting in air for 6, 12, 24, and 48 h. The enzyme activities including Î±-amylase and protease significantly increased in proportion to the germination period, and that of germinated quinoa(GQ) was the highest in the 24 h-germinated group and that of germinated amaranth(GA), in the 48 h-germination group. The Î±-amylase activity of GQ and GA was significantly higher than that of the control barley malt (M) and that of the germinated brown rice(GB) was also the highest in the 48 h-germination group but the lowest among all test groups. The protease activity also increased in proportion to the germination period, and that of both GQ and GA was significantly high in the 48 h-germination group. Similarly, Î³-aminobutyric acid (GABA), niacin, ascorbic acid, total poly phenol contents, and flavonoids significantly increased with respect to the germination time in Andean seeds with increase of antioxidant activity. Â In conclusion, optimal germination can stimulate bioactive changes in quinoa, amaranth and brown rice.Â